As estruturas sociais e econômicas do Império Romano do Ocidente e o estabelecimento do reino dos visigodos nas Galliae Aquitania e Narbonensis - Sartin, Gustavo Henrique Soares de Souza (2011)
In the year 376 of the Common Era, a tribe of Germanic warriors known as Tervingi , of Gothic extraction, crossed the Hister (Danube) river due south, entering the Roman Empire. They fled the Huns, a nomadic group that came plundering their way from the East. It did not take long for a conflict between the Roman imperial authorities and the refugees to begin. Peace was reached in 382 and, henceforth, the Tervingi would be officially foederati (allies) of the Romans, gaining the right to remain an autonomous tribe inside the borders of the Empire. For the next thirteen years the Tervingi warriors fought beside the Roman imperial armies in every major conflict. Nevertheless, after the death of the emperor Theodosius I in 395, their relations deteriorated severely. In theory, the Tervingi remained Roman allies; in practice, they begun to extort monies and other assets from the emperors Honorius and Arcadius. The sack of Rome by the Tervingi king Alaric in 410 was both the culmination and the point of inflection of this state of affairs. During the 410s the Tervingi warriors would fought again beside the Roman Imperial armies and be rewarded with a piece of land in the southwestern portion of the Gallic diocese. Dubbed Visigoths , they would remain trusted Roman allies throughout the next decades, consolidating their own kingdom in the process. This dissertation deals not only with the institution of the Visigothic kingdom in the southwestern portion of the Galliae but also with the social and economic conditions that hindered the Roman ability to defend their territory by themselves, hence opening opportunities for foederati like the Tervingi to carve out a piece of it for themselves.